Synthesis and Biological Evaluation of A Series of (Benzo[d]thiazol-2-yl) Cyclohexanecarboxamides and (Benzo[d]Thiazol-2-yl)Cyclohexanecarbothioamides - Nam, Nguyen H.; Phuong Dung, Phan Thi; Thuong, Phuong Thien; Hien, Tran Thi (Medicinal Chemistry, 2010)
A series of benzothiazole derivatives including N-(benzo[d]thiazol-2-yl)cyclohexanecarboxamides (2a-g) and N-(benzo[d]thiazol-2-yl)cyclohexancarbothioamides (3b-d) have been synthesized and evaluated for cytotoxic and antimicrobial activities. Two compounds including N-(6-ethoxybenzo[d]thiazol-2-yl)cyclohexanecarboxamide (2c) and N-(6- ethoxybenzo[d]thiazol-2-yl)cyclohexanecarbothiamide (3c) demonstrated significant cytotoxicity against three cancer cell lines (A549, MCF7-MDR and HT1080) while most of compounds exhibited moderate inhibitory effects on the growth of Staphyllococcus aureus and some other fungi.
Keywords: cytotoxicity